Acidic electrolyzed water efficiently improves the flavour of persimmon (Diospyros kaki L. cv. Mopan) wine. (15th April 2016) - Zhu, Wanqi; Zhu, Baoqing; Li, Yao; Zhang, Yanyan; Zhang, Bolin; Fan, Junfeng
Highlights: This is the first report to apply the electrolyzed water into food processing. The acidic water could improve persimmon wine flavor. The acidic water extract contains a great number of amino acids which generate esters. Abstract: The ability of acidic (AcW) and alkaline electrolyzed waters (AlW) to improve the flavour of persimmon ( Diospyros kaki L.) wine was evaluated. Wines made with AcW (WAcW) were significantly better than wines made with AlW or pure water (PW) in aroma, taste, and colour. Volatile analysis showed that WAcW has high alcohol and ester contents, including 2-phenylethanol, isopentanol, isobutanol, ethyl dodecanoate, phenethyl acetate, and butanedioic acid diethyl ester. The total amino acid content of persimmon slurry soaked with AcW reached 531.2 mg/l, which was much higher than those of the slurries soaked in AlW (381.3 mg/l) and PW (182.7 mg/l). The composition of major amino acids in the AcW-soaked slurry may contribute to the strong ester flavour of WAcW. This is the first report to suggest that electrolyzed functional water (EFW) can be used to improve wine flavour, leading to the possible use of EFW in food processing.